Nonalcoholic Cirrhosis Increased Risk of Digestive Tract Malignancies: A Population-Based Cohort Study. Issue 49 (December 2015) - Sun, Li-Min; Lin, Ming-Chia; Lin, Cheng-Li; Liang, Ji-An; Jeng, Long-Bin; Kao, Chia-Hung; Lu, Chiao-Yi
Abstract : Abstract: Alcoholic cirrhosis is generally accepted as a risk factor for hepatocellular carcinoma (HCC) development; however, little research has examined the relationship between nonalcoholic cirrhosis (NAC) and HCC. Thus, the aim of this study was to investigate whether NAC is associated with the risk of HCC and extrahepatic malignancies in Taiwan. We conducted a populated-based retrospective cohort study by using data from the Taiwan National Health Insurance (NHI) program. A total of 2109 patients with NAC were identified from the NHI database between 2000 and 2011. For a control group, 4 patients without NAC were frequency-matched with each NAC patient according to sex, age, and index year. We used Cox proportional hazards regression analysis to calculate adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) and determine the effects of NAC on cancer risk. The overall cancer risk was significantly higher in patients with NAC compared with those without NAC, and this association was consistent among age, sex, and comorbidity groups. The risk of developing HCC was remarkably high in the NAC group compared with in the control cohort (aHR = 122.7, 95% CI = 68.4–220.1); significantly higher risks of extrahepatic malignancies were observed in patients with digestive tract cancers and hematological malignancies. Further analyses stratified according sex, age, and follow-up duration revealed various patterns among the cancer types. The results indicate that patients with NAC in Taiwan have higher risks of HCC, digestive tract cancers, and hematological malignancies.